A DINASTIA OMRIDA: Reconstrução do Primeiro Estado Independente de Israel a partir da Bíblia e da Arqueologia - MENDONCA, ELCIO VALMIRO SALES DE (2017)
This research aims to analyze the Omride Dynasty as the founder of the first independent state of Israel in the ninth century BCE. This was the only time in history that Israel rules completely independently. Instead of being dominated, it was Israel who dominated. The kings of the Omride Dynasty expanded their territory, reaching the shores of the Mediterranean Sea, southern Syria, Transjordan and dominating over Judah. The founding of Samaria by Omri was the beginning of the first Israelite state. Omri built the city and made great works by uniting various architectural aspects and innovating with others, in a way that formed an architectural model for all buildings omridas by the vast territory. Northern Israel has all the characteristics of a developed state, according to the theories of the establishment of the states of Childe and Liverani. Sumptuous palaces, public and administrative buildings, specialized labor, collection of taxes, temples, surplus production, industries, body of scribes and developed writing. Judah had none of this, on the contrary, during the ninth century BCE, was small and without resources. Judah only becomes a developed state in the eighth century BCE, after Israel North was undone by the Assyrians. But despite all this, the Omride Dynasty is seen with the worst, most sinful and most perverse of all, its kings, especially Omri and Ahab, are evaluated in the biblical narratives, as the worst kings of Israel. This is because the history of Israel as we have it in the Bible was edited and compiled by Judah, when Northern Israel was destroyed, this favored Judah in biblical history. This research intends to do the opposite way, understanding the history of Israel from Northern Israel. And for that, the method used will be the exegetical analysis and the analysis of the archaeological findings. Exegesis with archeology to unravel the history of northern Israel from the ninth century BCE, which was not told in the biblical texts. For this, study visits were carried out in almost all the sites analyzed in this research (sites of Israel, Palestine and Jordan), excavations were also carried out at the archaeological site of Tel Megiddo (2016), with archaeologist Israel Finkelstein, one of the references of this search. As for the results, Israel North was in fact the first Israeli state, and the only one in all of Israel's history to exist and govern independently. The vast territory dominated by the Omride Dynasty is practically the same as the United Monarchy of David and Solomon. There is a strong possibility that the idea of the United Monarchy came from the memories of a powerful, prosperous and extensive kingdom that ruled North and South, Transjordan, and reached Syria, which had strong trade links with the Phoenician. At last, the only kingdom that did all this, was the one of the omrida dynasty.